ANALISIS PENGARUH PENANAMAN MODAL ASING, PENANAMAN MODAL DALAM NEGERI, DAN EKSPOR TOTAL TERHADAP PERTUMBUHAN EKONOMI - Sukandriah Sulistiawati; Made Siti Sundari; Idfi Setyaningrum (Perpustakaan Universitas Surabaya, 2018)
This study aims to analyze the influence of foreign investment, domestic investment, and total exports to Indonesia’s economic growth in the period 1990-2015. Using a quantitative approach and analyzed using OLS (Ordinary Least Square). Methotds of data used in this research is secondary data from 1990-2015. The findings of this investigation show that economic growth has a negative and significant effect on foreign investment, domestic investment, and total exports.